IMPLEMENTASI TEKNOLOGI PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI MAN 1 BARRU - Syahril, Muhammad; Suarga , Suarga; Wahyuddin, Wahyuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of learning technology in improving students’ learning outcomes at MAN 1 Barru. The research employed a descriptive qualitative approach using a field research design. The participants consisted of the principal, vice principal, teachers, and students. Data were collected through observation, interviews, and documentation. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques, while data validity was ensured through source, technique, and time triangulation. The findings indicate that the implementation of learning technology at MAN 1 Barru has been carried out through the functions of planning, implementation, supervision, and evaluation. The technologies utilized include Smart TVs, internet facilities, and various digital learning media that support the teaching and learning process. The use of these technologies has proven effective in increasing students’ motivation, participation, and understanding of learning materials, which positively impacts their learning outcomes. This is reflected in the students’ average academic achievement, which exceeded the Minimum Mastery Criteria (KKM) at all grade levels. However, the implementation of learning technology still faces several challenges, including the limited number of Smart TVs, unequal internet access, and the potential misuse of digital devices by students. To address these challenges, the school has undertaken various efforts, such as improving technological infrastructure, expanding digital learning facilities, enhancing internet connectivity, and strengthening supervision during the learning process. The study concludes that the implementation of learning technology plays a significant role in improving the quality of the learning process and students’ learning outcomes at MAN 1 Barru.